(untitled) (Journal of Mathematics Mechanics and Computer Science, 2012)
In presented article the problems of multiple alignment of nucleotide sequences and dendrogram construction are considered. During the conducted research by the author the following results were received: • the mathematical model of multiple alignment of nucleotide and amino-acid sequences is developed; • the algorithm of multiple alignment, constructed on the basis of algorithm of Needleman- Wunsch which was modified for processing of big data files with help of parallelization of treatment process by means of MPJ (Java MPI), is developed and analyzed; • the algorithm of dendrogram construction, representing modification of algorithms of UPGMA (Unweighted Pair Group Method with Arithmetic Mean) and NJ (Neighbour Joining) with possibility of parallelization of data processing, is developed; • program realization of algorithm of multiple alignment and dendrogram construction in the Java language with use of means of MPI is executed; • results of work of the program were tested on data on the nucleotide sequences provided by staff of the biotechnology department of Kazakh NU named al-Farabi.